Serum Albumin Before CRRT Was Associated With the 28- and 90-Day Mortality of Critically Ill Patients With Acute Kidney Injury and Treated With Continuous Renal Replacement Therapy - Lv, Junhua; Wang, Hai; Sun, Baoni; Gao, Yanxia; Zhang, Zhenglinag; Pei, Honghong (Frontiers in Nutrition, 2021)
Introduction: Although low serum albumin (ALB) may worsen acute kidney injury (AKI), additional study is needed to establish the connection between ALB and the prognosis of critically ill patients with AKI and treated with CRRT. Methods: A secondary analysis of a bi-center, retrospective and observational study including critically ill patients with AKI and treated with CRRT from January 2009 to September 2016. Univariate analysis, multi-factor regression analysis, sensitivity analysis, and curve-fitting analysis were applied to explore the association of ALB with the 28-day and 90-day mortality of critically ill patients with AKI and treated with CRRT, and the removal efficiency of serum phosphorus. Results: From January 2009 to September 2016, 1132 cases with AKI and treated with CRRT met the inclusion criteria and enrolled in this study. We found that the higher Alb before CRRT, the lower the 28-day and 90-day mortality of patients with AKI and treated with CRRT, the higher removal efficiency of serum phosphorus, the adjusted HR value for 28-day mortality in the four models were separately 0.92 (0.90, 0.95), 0.91 (0.89, 0.94), 0.92 (0.89, 0.95) and 0.92 (0.89, 0.95); the adjusted HR value for 90-day mortality in the four models were 0.91 (0.89, 0.94), 0.92 (0.89, 0.95), 0.92 (0.89, 0.95) and 0.92 (0.89, 0.96); the adjusted OR value for removal efficiency of serum phosphorus in the four models were separately -0.04 (-0.07, -0.01), -0.05 (-0.08, -0.01)，-0.04 (-0.08, -0.01) and -0.04 (-0.08, -0.01). Sensitivity analysis and curve-fitting analysis also showed that Alb before CRRT was correlated with the 28-day and 90-day mortality of critically ill patients with AKI and treated with CRRT and the removal efficiency of serum phosphorus. Conclusion: The higher the serum ALB before CRRT, the lower the mortality of critically ill patients with AKI and treated with CRRT, and the higher the clearance efficiency of serum phosphorus.